Avaliação da qualidade paisagística e dos equipamentos para o uso turístico no Parque do Ingá, Maringá, Brasil - Nigro, Giuliano Torrieri (2016)
Amid the discussion of the importance of urban green areas, specifically in urban parks in the context of cities, this study seeks to analyze the landscape as an important resource of tourism. The objective was to perform valuation analysis of the landscape and qualitative assessment of the Ingá Park facilities, located in the city of Maringa, Parana. It was intended to assess the potential of green area for tourism, analyzing the existing infrastructure and equipment conditions, check the landscape quality for tourist use, and to identify the sites of greatest gradient visitation and greater scenic beauty. The two methodological steps allowed to assess the tourism potential of the Inga Park. The first examined the visual quality objective, through the direct method, assigning values to 30 photographs, previously chosen randomly. These photographs were selected in three groups (high quality, medium quality and low quality), choosing the two photos that represented the best and worst placed of each class in order to select six photos for subjective analysis, through interviews, defining thus, the visual preference of tourists. The second methodological step allowed us to outline a diagnosis of conservation and adaptation conditions of all existing equipment in the park, quantifying and subsequently assigning notes to the qualitative analysis of these. This methodology has proven effective in identifying the points of greatest tourist potential of the park. There was no possibility to provide a relationship between the profile of the respondents and the preference of this landscape, but it was possible to establish a pattern of preference landscape guided by the choice of photographs that represented greater organization and harmony of the elements. The union of the two methodological steps concluded that the attractive Jardim Japonês and Gruta Nossa Senhora da Glória are the points of greatest tourist potential.